Formation of Magnesium Carbonates on Earth and Implications for Mars. Issue 7 (12th July 2021) - Scheller, Eva L.; Swindle, Carl; Grotzinger, John; Barnhart, Holly; Bhattacharjee, Surjyendu; Ehlmann, Bethany L.; Farley, Ken; Fischer, Woodward W.; Greenberger, Rebecca; Ingalls, Miquela; Martin, Peter E.; Osorio‐Rodriguez, Daniela; et al.
Abstract: Magnesium carbonates have been identified within the landing site of the Perseverance rover mission. This study reviews terrestrial analog environments and textural, mineral assemblage, isotopic, and elemental analyses that have been applied to establish formation conditions of magnesium carbonates. Magnesium carbonates form in five distinct settings: ultramafic rock‐hosted veins, the matrix of carbonated peridotite, nodules in soil, alkaline lake, and playa deposits, and as diagenetic replacements within lime—and dolostones. Dominant textures include fine‐grained or microcrystalline veins, nodules, and crusts. Microbial influences on formation are recorded in thrombolites, stromatolites, crinkly, and pustular laminites, spheroids, and filamentous microstructures. Mineral assemblages, fluid inclusions, and carbon, oxygen, magnesium, and clumped isotopes of carbon and oxygen have been used to determine the sources of carbon, magnesium, and fluid for magnesium carbonates as well as their temperatures of formation. Isotopic signatures in ultramafic rock‐hosted magnesium carbonates reveal that they form by either low‐temperature meteoric water infiltration and alteration, hydrothermal alteration, or metamorphic processes. Isotopic compositions of lacustrine magnesium carbonate record precipitation from lake water, evaporation processes, and ambient formation temperatures. Assessment of these features with similar analytical techniques applied to returned Martian samples can establish whether carbonates on ancient Mars were formed at high or low temperature conditions in the surface or subsurface through abiotic or biotic processes. The timing of carbonate formation processes could be constrained by 147 Sm‐ 143 Nd isochron, U‐Pb concordia, 207 Pb‐ 206 Pb isochron radiometric dating as well as 3 He, 21 Ne, 22 Ne, or 36 Ar surface exposure dating of returned Martian magnesium carbonate samples. Plain Language Summary: Magnesium carbonate minerals rarely form large deposits on Earth and because they constitute such a small proportion of the terrestrial carbonate record in comparison to calcium‐rich carbonates, they have received little attention. In contrast, the largest carbonate deposit detected on Mars has magnesium carbonate, and it has been detected at the landing site of the 2020 mission where the Perseverance rover will collect samples for return to Earth. We synthesized the field observations and laboratory experiments that pertain to magnesium carbonates formed on Earth and find that they form in five types of environments as follows: within veins or in the bulk volume of magnesium‐rich rocks, soils, alkaline or salty lakes, and as replacements of previously formed calcium‐rich carbonate minerals. Conceptually, these environments may be analogs for ancient Martian magnesium carbonate‐forming environments. Magnesium carbonates formed in some environments are capable of preserving remnants of microbes, especially if magnesium carbonates formed characteristic large‐scale clotted or vertical column shapes or microscale spherical and laminated textures. If life had ever originated on Mars, these would be key materials to investigate for biosignatures. Finally, a number of analytical techniques are discussed that can be performed on magnesium carbonate rocks collected by Perseverance when returned to Earth. Key Points: On Earth, magnesium carbonates of distinct textures form in ultramafic rock hosted veins, listvenites, soils, alkaline lakes, and playas The isotopic and elemental composition of terrestrial magnesium carbonate reveal timing and chemistry of fluid conditions Through the Mars 2020 sample return mission, the reviewed methods can be used to analyze carbonate‐forming conditions on ancient Mars